Effect of germination on lignan biosynthesis, and antioxidant and antiproliferative activities in flaxseed (Linum usitatissimum L.). (15th August 2016) - Wang, Hong; Wang, Junhong; Guo, Xinbo; Brennan, Charles Stephen; Li, Tong; Fu, Xiong; Chen, Gu; Liu, Rui Hai
Highlights: Evaluating transcriptional expression patterns of lignan biosynthesis in flaxseed. Flavonoid content increased 55-fold in flaxseed after germination. Germination enhanced flax lignan accumulation in flaxseed. Germination enhanced the antioxidant and antiproliferative activity in flaxseed. Abstract: Flaxseed is one of the richest seed sources of lignan and other bioactive compounds. The present study characterized lignan biosynthesis and potential health benefits in flaxseeds during 10-day germination. The transcription levels of lignan biosynthesis, along with variation of bioactivities, including cellular antioxidant activity and antiproliferative activity of flaxseed sprouts during germination, were studied. The results showed that 8-day germination brought about a 6.3-fold increase in secoisolariciresinol diglucoside and 4.5-fold increase in secoisolariciresinol compared to ungerminated flaxseeds. The highest amount of total phenolics and total flavonoids were found in 10-day geminated flaxseed, namely a 5.6-fold and 55-fold increase compared to ungerminated flaxseed. Transcription analysis revealed that five key-encoding genes in the lignan biosynthetic pathway were up-regulated during germination. Furthermore, the highest antioxidant and antiproliferative activities were found on day 10. These findings suggest that germination for 8–10 days leads to optimal lignan production and potential health benefits if incorporated into the human diet.